The development of co-speech gesture in the communication of children with autism spectrum disorders. (December 2013) - Sowden, Hannah; Clegg, Judy; Perkins, Michael
Abstract: Co-speech gestures have a close semantic relationship to speech in adult conversation. In typically developing children co-speech gestures which give additional information to speech facilitate the emergence of multi-word speech. A difficulty with integrating audio-visual information is known to exist for individuals with Autism Spectrum Disorder (ASD), which may affect development of the speech-gesture system. A longitudinal observational study was conducted with four children with ASD, aged 2;4 to 3;5 years. Participants were video-recorded for 20 min every 2 weeks during their attendance on an intervention programme. Recording continued for up to 8 months, thus affording a rich analysis of gestural practices from pre-verbal to multi-word speech across the group. All participants combined gesture with either speech or vocalisations. Co-speech gestures providing additional information to speech were observed to be either absent or rare. Findings suggest that children with ASD do not make use of the facilitating communicative effects of gesture in the same way as typically developing children.